PENGARUH DAYA TARIK WARNA PERANGKAP TERHADAP HAMA LALAT BUAH (Diptera:Tephritidae) PADA PERTANAMAN TOMAT (Solanum lycopersicum L.) - Iklima, Ilma; Yunus, Moh.; Nasir, Burhanuddin (AGROTEKBIS, 2018)
Of 19 types of vegetables, tomato was the one that produced the largest in 2014.  The production was 10,731 tons harvested from an area of 2,137 ha.  However, it is a decrease from the production in 2011 which was 65,120 tons from an area of 5,745 (BPS, 2015). The decline in yields and productivity of tomatoes is caused by Bactocera sp. fruit fly infestation. The purpose of this study was to determine the ability of various traps having different colors to capture fruit fly in tomato plants (Solanum lycopersicum L.). This research was done in Sidera village, Sigi Biromaru sub district, Sigi regency of Central Sulawesi province, from June to August 2016. This study used a Randomized Block design (RAK) consisting of five treatments with five replicates.  The yellow trap caught most fruit flies ranging from 9.60 to 48.00 flies leading to low intensity attacks of 14% to 18% with the tomato production of 0.58-0.95 tons/ha.  The lowest number of fruit flies caught was by the transparent trap ranging  from 3.40 to 15.60flies indicating a higher intensity attacks of 20% to 36% and resulting in lower tomato production of 0.46 to 0.60 tons/ha.